Food Safety Risk Analysis of Food Supply Chain in Small and Medium Enterprises (Case Study: Supply Chain of Fish) - Catur Wahyuni, Hana; Sumarmi, Wiwik; Agustini Saidi, Ida (International Journal of Engineering and Technology, 2018)
Food safety is an important element for human health. This study aims to identify risk and risk priority in the food supply chain. The case study used is a supply chain of fish crackers in SMEs. Data collection is done through observation and interview. Data processing is performed by calculating the likelyhood (L) and Impact (I) values. The results showed there were 6 actors in the supply chain of fish crackers, and 14 types of risk event. Based on the value of risk score known that the production environment and production equipment is the risk event that has the highest score. Therefore, production environment and production equipment is a priority risk that requires mitigation measures.Â Â